PENGARUH KOMPETENSI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA KANTOR PEGADAIAN KOTA PROBOLINGGO DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING - Firdaus, Aditya Abzar; Karnadi, Karnadi; Fandiyanto, Randika (Fakultas Ekonomi dan Bisnis, 2023)
The purpose of this research is to analyze the influence of variablesThe Influence of Competence and Compensation on Employee Performance at Pawnshops in Probolinggo City With Motivation as an Intervening Variable. By using the Partial Least Square (PLS) structural equation model. The results of the direct effect hypothesis test using the Smart PLS 3.0 application. Competence has a significant positive effect on Motivation (H1 is accepted), Compensation has a significant positive effect on Motivation (H2 is accepted), Competence has a significant positive effect on Employee Performance (H3 is accepted), Compensation has a significant positive effect on Employee Performance (H4 is accepted), Motivation has a significant positive effect on Employee Performance (H5 is accepted), Competence has a significant positive effect on Employee Performance through Motivation (H6 is accepted), and Compensation has a positive but not significant effect on Employee Performance through Motivation (H7 is rejected).